The portfolio structure of German households: A multinomial fractional response approach with unobserved heterogeneity - Gideon Becker (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
What determines the risk structure of financial portfolios of German households? In this paper we estimate the determinants of the share of financial wealth invested in three broad risk classes. We employ a new econometric approach - the so called fractional multinomial logit model - which allows for joint estimation of shares while accounting for their fractional nature. We extend the model to allow for unobserved heterogeneity across households via maximum simulated likelihood. We find that self-assessed appetite for risk as well as the level of wealth have strong positive effects on the riskiness of the average household's portfolio. These findings largely stay true even after we control for the potential confounding effects of unobserved differences across households via correlated random effects.
urn:nbn:de:bsz:21-dspace-574646
Keywords: C15; C33; C35; C51; C58; D14; G11; 330; household finance; portfolio composition; non-linear panel data model; fractional response model; unobserved heterogeneity